2014
DOI: 10.1080/00396338.2014.920145
|View full text |Cite
|
Sign up to set email alerts
|

Russian Military Capabilities after 20 Years of Reform

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
0
9
0
3
Order By: Relevance
“…It can be seen that by 2014 the share had reached 4.5% of GDP, very high by international standards, and almost 5.5% in 2015. This puts Russia in a limited 2 On the Serdyukov reforms, see Klein (2012) and Renz (2014). Note: The fall in GDP with the global financial-economic crisis accounts for the spike in 2009.…”
Section: The Rapid Growth Of Military Spendingmentioning
confidence: 99%
“…It can be seen that by 2014 the share had reached 4.5% of GDP, very high by international standards, and almost 5.5% in 2015. This puts Russia in a limited 2 On the Serdyukov reforms, see Klein (2012) and Renz (2014). Note: The fall in GDP with the global financial-economic crisis accounts for the spike in 2009.…”
Section: The Rapid Growth Of Military Spendingmentioning
confidence: 99%
“…Regarding the first event, the restoration of Russia's credibility as a global great power has been a major focus for the Kremlin since its unconvincing intervention in Georgia in 2008 (bryce-Rogers, 2013;Renz, 2014). Although the war lasted a mere five days and resulted in a clear Russian victory, a glaring deficiency (even compared to the Georgians) in "information technology, unmanned aerial vehicles and precision-guided munitions" was exposed (Renz, 2014, p. 65).…”
Section: Introductionmentioning
confidence: 99%
“…Vendil Pallin andWesterlund (2009, p. 401) argue that the Georgia conflict demonstrated that Russia's "precision weapons cannot compete with Western versions and its C4ISR capabilities (command, control, communications, computers, intelligence, surveillance and reconnaissance) are in need of upgrading. " Shortly after the conflict, Russia's then minister of defense, Anatoly Serdyukov, began an ambitious modernization of its military power with the aim of being 70 percent modernized by 2020, relative to the 10-15 percent level of modernization during the Georgian conflict (Renz, 2014). In addition to the modernization of its capabilities, Russia's post-Georgia strategy has also emphasized smaller, more efficient armed forces as well as improved training and education (bryce-Rogers, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(But it should also be noted that many weaknesses remain. It is therefore important not to exaggerate the impact of Russia's military modernization program [Renz 2014]. )…”
Section: The Return Of the Military-industrial Complexmentioning
confidence: 99%